1983
DOI: 10.1203/00006450-198308000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Lactose Assimilation by Full-Term Infants: Relation of [13C] and H2 Breath Tests with Fecal [13C] Excretion

Abstract: Neutral P-galactosidase (lactase) located in the bush border of adults varied from 0.950-0.997; the ratio of the cumulative % dose the small intestinal enterocyte is the enzyme responsible for the [13Cj (cum % [13Cj) to the cumulative % dose [14cj (cum % [14cj) hydrolysis of lactose, which is the rate limiting step in lactose ranged from 0.89-1.15. Nineteen full-term infants (40.1 + 0.9 wk absorption (8, 11). Lactase, unlike sucrase and maltase, remains gestation) were subsequently studied. On day 1 baseline b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 8 publications
1
17
0
1
Order By: Relevance
“…A possible reason may be related to the diet consumed by the human host at different stages of life. To illustrate, dietary carbohydrates that are consumed by infants comprise mainly disaccharides (lactose) and oligosaccharides [18,19], which are in turn rapidly hydrolyzed to form galactose and glucose monosaccharides [20,21]. A portion of these monosaccharides becomes available for the commensal microbiota, and because Bifidobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason may be related to the diet consumed by the human host at different stages of life. To illustrate, dietary carbohydrates that are consumed by infants comprise mainly disaccharides (lactose) and oligosaccharides [18,19], which are in turn rapidly hydrolyzed to form galactose and glucose monosaccharides [20,21]. A portion of these monosaccharides becomes available for the commensal microbiota, and because Bifidobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the application of 13 C-labelled substrates for diagnostic breath tests is directed to diseases of the stomach, liver, pancreas, and small bowel (Ghoos et al, 1993;Klein and Klein, 1985;McLean et al, 1983; Mundlos, Kühnelt and Adler, 1990; Murphy et al, 1990). The non-invasive lactulose H 2 -breath test is widely used for quantifying the OCTT based on the metabolic release of H 2 from the non-absorbable disaccharide lactulose in the human colon.…”
Section: Discussionmentioning
confidence: 99%
“…59 It has been demonstrated that malabsorbed lactose is salvaged by the distal ileal and colonic lactic acid bacteria. 60 Lactic acid bacteria are Gram-positive, e.g. Lactobacillus, Bifidobacterium, Staphylococcus, Enterococcus, Streptococcus, Leuconostoc and Pediococcus and ferment lactose to produce lactate, hydrogen, methane, carbon dioxide and SCFAs.…”
Section: Intestinal Microflora Fermentation and Fermented Foodsmentioning
confidence: 99%